ACUTE RENAL FAILURE AFTER CARDIOPULMONARY BYPASS SURGERY - Khilji, Shahbaz Ahmad; Khan, Ammar Hameed (Journal of Ayub Medical College Abbottabad, 2004)
Background: Acute renal failure (urine output <0.5ml/kg/hr.) following cardiopulmonary bypass is an uncommon but highly lethal complication which arises in the setting of inadequate cardiac function and may be associated with multi-organ failure. Acute renal failure (ARF) after cardiopulmonary bypass occurs in about 8% of adult cardiac surgical patients with some preoperative renal impairment and in about 3-4% of patients with normal preoperative renal parameters. This study was conducted to determine the frequency of acute renal failure after cardiopulmonary bypass operations and to find possible risks factors. Methods: We analyzed the data of 500 consecutive patients who survived the first 24 hours after open heart surgery at Punjab Institute of Cardiology, Lahore as this is the minimum time to evaluate post-operative renal function, their morbidity, mortality and the main contributing risk factors, from July 2000 to Dec. 2000. The association between preoperative, intra-operative and postoperative variables and the development of ARF was assessed by multivariate logistic regression. Results: Of the 500 consecutive patients 35 (7%) patients developed acute renal failure (serum creatinine>2.5 mg/dl) and 102 (20.4%) patients developed acute renal dysfunction (serum creatinine 1.6-2.4 mg/dl). Positive risk factors noted in the development of ARF were age, raised preoperative blood urea and creatinine, diabetes mellitus, low cardiac output state, oligurea, total CPB time, total cross clamp time and significant hypotension during the procedure or during intensive care unit (ICU) stay. Mortality rate for established ARF was extremely poor (88.8 %) and there were only four (4) survivors among those requiring dialysis. Conclusions: Prevention of this disastrous complication appears to be better than treatment once it is fully established. However newer aggressive forms of early renal replacement / transplant therapies may have some promise. Key words: Acute Renal failure, CABG, Cardiopulmonary bypass surgery